Critique of your Work and Methods (A Self-Appraisal) - Morris, Fred C. (Journal of Engineering Education Transformations, 1994)
Teaching has been accorded professional status, and professional ethics dictate that the teacher be left largely to his own devices. Professional ethics, however, should not be used as a refuge for the incompetent, nor should they condone and protect poor practice.